Internalisasi Nilai Moderasi Beragama melalui Kegiatan Keagamaan di TPQ At Taqwa Purbalingga - Mochammad Sidqi Awaliya Rahman (Yayasan Literasi Sains Indonesia, 2026)
This study examines the internalization of religious moderation values through religious activities at TPQ At-Taqwa Purbalingga as a nonformal Islamic educational institution that plays a role in shaping students’ religious character from an early age. The study aims to analyze the process of internalizing religious moderation and the implementation of the four indicators of religious moderation formulated by the Ministry of Religious Affairs of the Republic of Indonesia, namely national commitment, tolerance, anti-violence, and accommodative attitudes toward local culture. This study employed a qualitative approach with a field research design. The formal object of this study is the internalization of religious moderation, while the material object focuses on religious activities conducted at TPQ At-Taqwa Purbalingga within the context of nonformal Islamic education. Data were collected through participatory observation, semi-structured interviews, and documentation, and were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the internalization of religious moderation is carried out through social habituation, teachers’ role modeling, collective interaction, and contextual religious experiences in the students’ daily lives. The four indicators of religious moderation are reflected in activities such as ziarah masyayikh and tadabbur alam, talaqqi learning and collective prayers, dialogical conflict resolution, and the use of Javanese Krama Halus in classroom interaction. This study concludes that TPQ functions not only as a space for Qur’anic learning but also as a strategic socio-religious environment for fostering moderate, tolerant, and adaptive students through experiential learning and social habituation.